O efeito da complexidade estrutural da fonte de nitrogênio no transporte de amônio em saccharomyces cerevisiae - Da Cruz, Sandra Helena [UNESP]; Cassio, Fernanda; Leão, Cecília; Ernandes, José Roberto [UNESP] (My University, 2001)
Ammonium transport in Saccharomyces cerevisiae is influenced by the structural complexity of the nitrogen source. Yeast cells were grown in minimum media containing glucose and nitrogen sources with structural complexity varying from single ammonium salt (ammonium sulfate) to free amino acids (casamino acids) and peptides (peptone). Ammonium transport was followed by potassium efflux and uptake of [14C] methylammonium by yeast cells grown upon differing nitrogen supplementation. Active transport of methylammonium is detected in cells grown in media supplemented with ammonium sulfate and peptone and the transport is not detected in cells grown on casamino acids. Kinetics of methylammonium uptake measured at differing growth time suggest that the transport process is more stable upon peptone supplementation. The results described in this work suggest that the structural complexity interferes with ammonium uptake in Saccharomyces cerevisiae and that supplementation with nitrogen source in a peptide form is not only more efficient for the transporter expression but also for the stability of the transport process.
Keywords: Ammonium transport; Nitrogen metabolism; Saccharomyces cerevisiae